P50-S State dependent changes in cortical reactivity: Comparison between transcranial and intracranial stimulation. Issue 7 (July 2019) - Pigorini, Andrea; Parmigiani, Sara; Russo, Simone; Mikulan, Ezequiel; Cattani, Anna; Sarasso, Simone; Fecchio, Matteo; Sartori, Ivana; Rubino, Annalisa; Amico, Federica; Gibbs, Steve; Comolatti, Renzo; et al.
Abstract : Background: Direct cortical perturbations had been used to study state-dependent changes in thalamocortical network. TMS combined with EEG has demonstrated consistent modifications among wakefulness, NREM sleep, and anesthesia; furthermore, these measurements resulted useful in the diagnosis and pathophysiological stratification of patients with disorders of consciousness. Methods: To corroborate the results obtained with noninvasive stimulations and to gain insight on their neurophysiological underpinnings, we compared the EEG responses elicited by TMS with the EEG and intracranial responses simultaneously recorded during Single Pulse Electrical Stimulation (SPES) in wakefulness and sleep. Results: We found consistent state-dependent changes occurring during sleep in both kind of stimulations: (1) a slowing of the EEG response; (2) an increase in the amplitude of the early evoked response; (3) a loss of stimulated-site-dependent differentiation, whereby the spectral variance across site-specific responses tends to converge on a stereotypical slow wave; (4) a constant decrease of the overall complexity of the spatiotemporal dynamics elicited by the perturbation; (5) an occurrence of a neuronal off-period during sleep, detected by the transient suppression of high frequencies. Conclusions: Although these state-dependent changes were consistent in the two types of stimulations, SPES can reach deep brain structures resulting in an increased variance across sites, and suggesting further regional specificity that cannot be captured by noninvasive stimulation and recordings. Taken together, these findings confirm and expand TMS-EEG results by providing fine brain description of neuronal dynamics that could also be involved in the study of loss and recovery of consciousness in brain-lesioned patients.